The Attitudes of the Political Parties of Northern Ireland Towards the Status of the Irish Border Settled in the Windsor Framework in 2023 (Politeja, 2025)
The 2016 Brexit referendum and the subsequent negotiations on the terms of the United Kingdom’s exit from the European Union have been the cause of the most serious crisis in the peace process in Northern Ireland since the signing of the Good Friday Agreement in 1998. At the heart of the crisis was the issue of the possible restoration of the Irish border (the so-called hard border option), which posed the threat of a return to conflict. During the political negotiations, a unique formula was adopted – the so-called Windsor Framework, modifying the Irish Protocol, which is an annex to the agreement between the United Kingdom and the European Union. The subject of this article is to present the attitudes of the largest political parties in Northern Ireland: Sinn Féin and the Democratic Unionist Party (DUP) as well as other parties towards this solution. The diverse approach to the adopted solutions regarding the Irish border is closely related to both the political profile of the parties and the complicated and turbulent history of the peace process in Northern Ireland.